The Effect of Capital Structure, Assets Structure and Sales Growth on Company Performance - Suci, Rochmalia Nur; Hazmi, Shadrina (Institut Bisnis dan Informatika Kesatuan, 2024)
This research aims to analyze the influence of Capital Structure, Asset Structure, and Sales Growth on Company Performance in Real Estate and Property sub-sector companies. The sampling method used in this research is the purposive sampling method. The samples obtained were 62 companies from 91 companies. Capital Structure is measured using the Debt-to-Equity Ratio (DER), Asset Structure is measured by dividing fixed assets by total assets, and Sales Growth is measured by comparing the difference between sales for the current year and the previous year with the sales of the previous year. The type of data used in this research is secondary data and the data analysis method uses classical assumption tests, multiple linear regression analysis, hypothesis testing and coefficient of determination tests. Based on the simultaneous test analysis of Capital Structure (X1), Asset Structure (X2), and Sales Growth (X3) simultaneously influence Company Performance. Then, based on partial test analysis, the Capital Structure variable (X1) has a significant negative effect on Company Performance, while Asset Structure (X2) and Sales Growth (X3) have no effect on Company Performance.